The Effect of Wetting on the Collapsibility and Shear Strengths of Tropical Residual Soils - Azmi, Nor Azwati (2008)
In Malaysia, almost 80% of its land is covered with residual soils, especially sedimentary and granitic residual soils. It is believed that these types of soil have a high possibility to collapse when wetted. The high rate of collapsibility is influenced by the climatic tropical factor, hot and high humidity throughout the year. Therefore, the main objective of this study is to identify the effect of wetting on the collapsibility and shear strength of the tropical residual soils. Two major tests employed in the study were the Double Oedometer and Double Shear Box tests. For each test, two different samples were tested; the first samples were the soils in their natural moisture condition and the second were inundated in water. The samples tested using the double oedometer test were allowed to be inundated in water for a few days under applied load until they achieved a steady state (the dial gauge reading remained constant) before another load was added. There were 20 samples in the situation before and after the inundated condition for the two major tests. Other than the rate of collapsibility and shear strength of these soils, other parameters such as void ratio, porosity, particle size distribution, dry density and bulk density were also observed. Other test such as the Scanning Electron Microscopic and X-Ray Diffraction Analysis were also carried out. From the result obtained, both type of soil collapse due to wetting however, calculated collapse potential indicates that the granitic residual soil is higher and having wider range as compared to sedimentary residual soil. After collapsing due to wetting, result from SEM analysis indicate that the soils sample structure become more compacted and voids between structure become smaller. On the other hand, result from shear strength test showed shear strength reduced vigorously after inundated especially in Granitic residual soil because the cohesion and friction angle reduced to more than 50% whereas much lesser in Sedimentary residual soil i.e. in the range of 30% to 40%.